Penerapan Metode Dmaic dalam Peningkatan Acceptance Rate untuk Ukuran Panjang Produk Bushing - Hartoyo, Ferdian; Yudhistira, Yudha; Chandra, Andry; Chie, Ho Hwi (Bina Nusantara University, 2013)
PT Argatama Multy Agung is one provider of metal cutting services using turret machine. The quality of metal cutting services offered are still questioned. The quality service intended is that the length accuracy of the outcome product meets the requirements of the requested length. The purpose of this study is to determine what factors lead to defects the goods length, as well as to provide the right solution that factors can be eliminated so that the number of defective products can be reduced. In this research authors implement Six Sigma methodology with an improved model of Define-Measure-Analyze-Improve-Control (DMAIC) to perform improvement in the services quality provided by PT Argatama Multy Agung. On the improvement phase Design Of Experiment (DOE) is used to find the machine configuration that can produce the best quality. From the research conducted, a significant increase of sigma is obtained.